Vitamin D Deficiency in Patients with Type 2 Diabetes Mellitus with and without Pulmonary Tuberculosis - Wahiduddin, Wahiduddin; Agung Pranoto; Sudjarwo , Sudjarwo (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Background: Vitamin D has a role in the body's calcium balance and immunodeficiency effects, and stimulates dendric cells, monocytes, T cells, macrophages in pathogenic microbes’ elimination. The variation occurrence as polymorphism on VDR might cause problem in production, transportation, and activity of vitamin D. The gap between the occurrence findings in previous studies shows that there are indication factors of VDR levels that probably associate with the T2DM range in comorbid with pulmonary tuberculosis. To determine vitamin D levels and factors associated with vitamin D deficiency in Type 2 Diabetes Mellitus (T2DM) patients with and without pulmonary Tuberculosis (TB). Method: The design of this study was cross-sectional. T2DM subjects with pulmonary TB were 45 people, and 43 people without pulmonary TB were 43 people. Sampling was done by consecutive sampling from October to December 2017. We collected data through interviews and examination of plasma vitamin D (25-OH) levels by ELISA. Data analysis using the Mann-Whitney test, and chi-square test with a confidence level of 95%. Result: There were 88 T2DM patients who met the inclusion criteria, consisting of 43 T2DM patients without pulmonary TB and 45 T2DM patients with pulmonary TB as the study subjects. There were differences in the distribution of T2DM subjects based on sex and BMI measurements. The mean plasma vitamin D levels in T2DM with pulmonary TB and T2DM without pulmonary TB were 20.08 ng/ml (SD ± 0.83 ng/ml) and 20.29 ng/ml (SD ± 0.81 ng/ml), respectively, we found no significant result in statistic (p = 0.287). Vitamin D deficiency was not associated with the incidence of pulmonary TB in T2DM, whereas female sex, age> 50 years, BMI ? 25.0 kg /m2, and duration of T2DM> 5 years were associated with vitamin D deficiency (p <0.05). This research has contributed in novel findings of the correlation between sex and BMI associated in duration of T2DM impacted the Vitamin D insufficiently. Conclusion: Sex, age, BMI, and duration of T2DM had a significant correlation with vitamin D deficiency in T2DM patients with and without pulmonary TB.